Correlation Between Platelets Count, Platelet Index and D-Dimer in Covid-19 Patients - Nelly Tolla; Rachmawaty Rachmawaty; Andi Salsa Anggeraini; Darmmawaty R; Faidah Nur (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2023)
Hypercoagulation in the alveoli of the lungs is one of the causes of death in SARS-CoV2 virus infection. Hypercoagulation is defined by an elevation in D-Dimer, which typically rises on the fifth day of therapy. This parameter is not available in all hospitals and is still relatively expensive in preventing premature death. Platelets count and indices are suggested to describe the thromboinflammatory condition in COVID-19 patients. This research is an observational analytic study with a cross-sectional study design in 59 COVID-19 patients treated at Hassanuddin University Hospital. The patients who are declared COVID-19 based on the results of radiological examinations and PCR swabs underwent routine blood tests and D-Dimer before undergoing therapy. Data were analyzed using the Spearmen test in SPSS version 26 to reveal the correlation between platelet count, platelet indices, and D Dimer in COVID-19 patients with severe and non-severe conditions.  Platelet count, platelet indices, especially MPV, and D-Dimer values were found to correlate in both groups COVID-19 using the Spearman rho correlation test (p 0.000) with strengths correlation between -44.6 and 60.5. There was a significant association between platelet count and MPV value with D-Dimer in COVID-19 patients.